Concentración de lactasa y glucosa en las propiedades fisicoquímicas y sensoriales del dulce de leche con pulpa de camote (Ipomoea batatas) - Zambrano Carranza, Jefferson Alejandro (2017)
In this research the concentrations of lactase (0.03 and 0.04%), and glucose (1, 2, and 3%) were evaluated in the improvement of physicochemical and sensorial properties of dulce de leche with pulp of sweet potato (Ipomoea batatas), an experimental design was used completely at random in accordance with bi-factorial (2 x 3), the experimental material was 3.873 g. Physicochemical parameters were evaluated: °Brix, loss by heating and consistency, microbiologically tested the existence of fungi/yeasts and sensory attributes were evaluated as: brightness, colour, aroma, texture and sweetness with judges not trained in a hedonic scale of 1-9 against a witness or control. Results showed that microbiologically T6 treatment exceeded the number of allowed by the standard INEN 700 cfu. However in the physico-chemical part T2 won best qualities in losses by heating (33.43%), consistency (1.57 cm2/s) and °Brix T1 (68,83%) earned a best qualities, sensually all treatments presented statistical differences with the witness, with the exception of attribute aroma. The unit cost to the best treatment T2 (0.03% of lactase + 2% glucose) in presentation of 250g equals $1.53; this leads to the conclusion that the factors studied (lactase and glucose) influence significantly in most variable responses and that the cost of production in the manufacture of the product is low.